Giants in tourism: captive conditions, industry trends, and animal welfare implications for Asian elephants in tourism from 2014 to 2020 - Green, Jennah; Schmidt-Burbach, Jan; Hartley-Backhouse, Lindsay (Frontiers in Ethology, 2025)
Asian elephants (Elephas maximus) are kept at commercial facilities as tourist attractions across many of their range states. Maintaining elephants in captivity presents a multitude of challenges for meeting their physical and behavioral needs as a wild species. Significant cause for concern for the welfare of elephants at tourism venues has previously been published and includes the need for severe restraint, limitations to nutritional variety, stressful interactions with visitors, and harmful practices of controlling the elephants, to name a few. This study presents data from the longest and most comprehensive assessment of captive conditions for Asian elephants in the tourism industry, to date. Researchers visited elephant tourism venues across Thailand, India, Laos, Cambodia, Nepal, Sri Lanka and Malaysia in 2014–2016 and 2019-2020. These were continuations of an earlier study in Thailand from 2009-2010, which allows a ten-year perspective. The most recent assessments documented 3,837 elephants kept at 357 tourism venues across these countries. Here we define trends observed across the industry in the period 2010–2019 and discuss the welfare concerns associated with the captive conditions documented during the study period. Our data indicate that while during the duration of the study animal welfare condition scores improved across almost all assessed welfare condition indicators, they remained low for the majority of elephants. There was a notable decrease in the frequency of venues offering elephant rides but a significant increase in other tourist experiences that allow direct visitor interaction with elephants, such as elephant washing and feeding. Despite fluctuating trends and some improvements in management, over 3,000 elephants still faced challenges to their welfare in 2020. Documented improvements to elephant tourism venues indicate a diversification of tourism experiences to cater to an emerging demand for ethical tourism activities, yet not an actual phase out of problematic practices. We hope our data can provide a snapshot of the conditions provided for the majority of captive Asian elephants, on a wide scale and over an extended time period, to provide a broad perspective of welfare within the captive elephant tourism industry as a whole.